AirConstellations: In-Air Device Formations for Cross-Device Interaction via Multiple Spatially-Aware Armatures - Marquardt, Nicolai; Henry Riche, Nathalie; Holz, Christian; Romat, Hugo; Pahud, Michel; Brudy, Frederik; Ledo, David; Park, Chunjong; Nicholas, Molly Jane; Seyed, Teddy; Ofek, Eyal; Lee, Bongshin; et al. (UIST'21: 34th Annual ACM Symposium on User Interface Software and Technology, 2021)
AirConstellations supports a unique semi-fixed style of cross-device interactions via multiple self-spatially-aware armatures to which users can easily attach (or detach) tablets and other devices. In particular, AirConstellations affords highly flexible and dynamic device formations where the users can bring multiple devices together in-air – with 2-5 armatures poseable in 7DoF within the same workspace – to suit the demands of their current task, social situation, app scenario, or mobility needs. This affords an interaction metaphor where relative orientation, proximity, attaching (or detaching) devices, and continuous movement into and out of ad-hoc ensembles can drive context-sensitive interactions. Yet all devices remain self-stable in useful configurations even when released in mid-air. We explore flexible physical arrangement, feedforward of transition options, and layering of devices in-air across a variety of multi-device app scenarios. These include video conferencing with flexible arrangement of the person-space of multiple remote participants around a shared task-space, layered and tiled device formations with overview+detail and shared-to-personal transitions, and flexible composition of UI panels and tool palettes across devices for productivity applications. A preliminary interview study highlights user reactions to AirConstellations, such as for minimally disruptive device formations, easier physical transitions, and balancing "seeing and being seen" in remote work.